AKSI SOSIAL DAN LINGKUNGAN STKIP AGAMA HINDU AMLAPURA BERBASIS PENGABDIAN MASYARAKAT DI DESA LEAN, BUNUTAN, KARANGASEM - Wiriawan, I Ketut (Penerbit Widina, Widina Media Utama, 2026)
Community service is an integral part of the Tri Dharma of Higher Education, aiming to bridge the academic world with the real needs of the community. This article aims to describe the implementation and impact of community service-based social and environmental action activities carried out in Lean Village, Bunutan District, Karangasem Regency. The community service method was implemented through a participatory approach, involving lecturers and students of the Hindu Teacher Training College of Amlapura, as well as the local community as the subjects of the activities. The activities included cooking together in residents' homes, distributing basic necessities to those in need, and cleaning the village environment. The results of the activities showed an increase in social awareness, a spirit of mutual cooperation, and increased public awareness of the importance of maintaining cleanliness and environmental sustainability. Furthermore, these activities also provided contextual learning experiences for students in implementing social and humanitarian values. It can be concluded that integrated social and environmental action based on community participation can have positive social and educational impacts and has the potential to become a model for sustainable community service in rural areas.ABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kepedulian sosial dan kesadaran lingkungan masyarakat Desa Lean, Kecamatan Bunutan, Kabupaten Karangasem. Program dilaksanakan oleh dosen dan mahasiswa STKIP Agama Hindu Amlapura dengan pendekatan partisipatif yang melibatkan masyarakat sebagai mitra kegiatan. Bentuk kegiatan meliputi memasak bersama di rumah warga, pembagian sembako kepada masyarakat yang membutuhkan, serta kegiatan bersih-bersih lingkungan desa. Hasil kegiatan menunjukkan terbangunnya semangat gotong royong, meningkatnya interaksi sosial yang harmonis, serta tumbuhnya kesadaran masyarakat terhadap pentingnya kebersihan dan kepedulian sosial. Selain memberikan manfaat langsung bagi masyarakat, kegiatan ini juga berkontribusi dalam penguatan karakter mahasiswa melalui pengalaman pembelajaran kontekstual. Kegiatan pengabdian ini dapat disimpulkan bahwa aksi sosial dan lingkungan yang terintegrasi mampu memberikan dampak positif secara sosial dan edukatif bagi masyarakat dan civitas akademika.